The image of the city in the information era - Ahmadpoor, Negar; Heath, Tim (2015)
This paper presents the early stages of a PhD research which attempts to analyze the effect of using digital mobile devices on the process of city imaging in The Information Era. Within this process, some guidelines are suggested in order to facilitate the design of the physical urban environment as well as the design of technologies with location-based systems and navigators.